2016
DOI: 10.1021/acs.nanolett.6b03857
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Wide Bandgap Perovskite Solar Cells by Tin Substitution

Abstract: Wide bandgap MAPb(IBr) perovskites show promising potential for application in tandem solar cells. However, unstable photovoltaic performance caused by phase segregation has been observed under illumination when y is above 0.2. Herein, we successfully demonstrate stabilization of the I/Br phase by partially replacing Pb with Sn and verify this stabilization with X-ray diffractometry and transient absorption spectroscopy. The resulting MAPbSn(IBr) perovskite solar cells show stable photovoltaic performance unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
187
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(196 citation statements)
references
References 35 publications
(79 reference statements)
7
187
0
Order By: Relevance
“…Furthermore, precursor engineering that either mixed individual Sn and Pb based precursors or blended with additives (such as chloride, Rb, and Cs) would be employed to tune the crystallization. These Sn‐Pb binary perovskite precursor films generally spin‐coated on poly(3,4‐ethylenedioxythiophene):poly(p‐styrene sulfonate) (PEDOT:PSS) substrates would be washed/immersed by anti‐solvents, including toluene, anisole or diethyl ether, and annealed . Meanwhile, Sn‐Pb binary perovskite films can be formed by two‐step solution‐process methods.…”
Section: Crystallization Properties and Applications Of Low‐bandgapmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, precursor engineering that either mixed individual Sn and Pb based precursors or blended with additives (such as chloride, Rb, and Cs) would be employed to tune the crystallization. These Sn‐Pb binary perovskite precursor films generally spin‐coated on poly(3,4‐ethylenedioxythiophene):poly(p‐styrene sulfonate) (PEDOT:PSS) substrates would be washed/immersed by anti‐solvents, including toluene, anisole or diethyl ether, and annealed . Meanwhile, Sn‐Pb binary perovskite films can be formed by two‐step solution‐process methods.…”
Section: Crystallization Properties and Applications Of Low‐bandgapmentioning
confidence: 99%
“…Notably, partial Sn substitution (25 mol%) in the wide‐bandgap MAPb(I/Br) 3 perovskite system could improve the phase stability of I/Br‐based perovskites . Similarly, wide‐bandgap CsPb 0.9 Sn 0.1 IBr 2 perovskite films could stabilize the perovskite phase and enhance endurance against heat and moisture .…”
Section: Introductionmentioning
confidence: 99%
“…However, recently several studies, using different perovskite systems, have shown a good correlation between reduced microstrain and enhanced optoelectronic properties. [16,43,44] We suggest that either microstrain itself, or the crystal defects responsible for microstrain, or both are closely related to the defects responsible for negating high optoelectronic quality in these materials. Hence, with respect to attempting to realize an ideal perovskite semiconductor, minimizing microstrain in the polycrystalline thin films is likely to be a good metric to assess, and lead to improved optoelectronic quality.…”
mentioning
confidence: 94%
“…When exposed to moisture, the perovskite structure tend to hydrolyse6, undergoing irreversible degradation and decomposing back into the precursors, for example, the highly hygroscopic CH 3 NH 3 X and CH(NH 2 ) 2 X salts and PbX 2 , with X=halide, a process that can be dramatically accelerated by heat, electric field and ultraviolet exposure78. Material instability can be controlled to a certain extent using cross-linking additives9 or by compositional engineering10, that is, adding a combination of Pb(CH 3 CO 2 ) 2 ·3H 2 O and PbCl 2 in the precursors11 or using cation cascade, including Cs and Rb cations, as recently demonstrated23, to reduce the material photo-instability and/or optimize the film morphology. However, solar cell degradation is not only due by the poor stability of the perovskite layers, but can be also accelerated by the instability of the other layers of the solar cell stack.…”
mentioning
confidence: 99%